Expression levels of Lyn, Syk, PLCγ2 and ERK in patients with chronic lymphocytic leukemia, and higher levels of Lyn are associated with a shorter treatment-free survival. Issue 6 (1st June 2013) - Wang, Yin-Hua; Fan, Lei; Wang, Li; Zhang, Run; Zou, Zhi-Jian; Fang, Cheng; Zhang, Li-Na; Li, Jian-Yong; Xu, Wei
Abstract: There is now strong evidence that B-cell receptor (BCR) signaling plays a major role in the development of chronic lymphocytic leukemia (CLL). The purpose of this study was to investigate the expression levels of some of the molecules involved in the signaling cascade originating from the BCR (Syk, Lyn, PLCγ2, ERK) and analyze possible correlations of mRNA levels with biological/clinical features. Our study population consisted of 92 consecutive patients with newly diagnosed CLL. Several genes of BCR signaling (Lyn, Syk, PLCγ2 and ERK) and ZAP-70 were measured by quantitative polymerase chain reaction (qPCR). The signaling molecules of BCR were strongly associated with each other, and ZAP-70 correlated well with Lyn, Syk, PLCγ2 and ERK. Associations between treatment response and Lyn, Syk, PLCγ2 and ERK were not found. Moreover, a higher level of Lyn mRNA was associated with a shorter treatment-free survival (TFS) (univariate analysis only; multivariate Cox analysis showed that only ZAP-70 and Binet stage were independent prognostic factors and associated with TFS). Though Lyn was not an independent prognostic factor, it still might be a new therapy target of CLL. BCR signaling provides perspectives for future development of an exciting new class of kinase inhibitors.